2014
DOI: 10.1126/scitranslmed.3007280
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy for Wiskott-Aldrich Syndrome—Long-Term Efficacy and Genotoxicity

Abstract: Wiskott-Aldrich syndrome (WAS) is characterized by microthrombocytopenia, immunodeficiency, autoimmunity, and susceptibility to malignancies. In our hematopoietic stem cell gene therapy (GT) trial using a γ-retroviral vector, 9 of 10 patients showed sustained engraftment and correction of WAS protein (WASP) expression in lymphoid and myeloid cells and platelets. GT resulted in partial or complete resolution of immunodeficiency, autoimmunity, and bleeding diathesis. Analysis of retroviral insertion sites reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
370
1
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 496 publications
(384 citation statements)
references
References 58 publications
9
370
1
4
Order By: Relevance
“…Finally, we note that these mutations occur within the same intron as retroviral integration sites described in 2 cases of gene therapyinduced T-ALL (supplemental Figure 8). 22,26 This raises the possibility that formation of aberrant promoters and enhancers, either by mutation or retroviral insertion, occur at preferred rather than random sites in the noncoding genome. For personal use only.…”
Section: Org Frommentioning
confidence: 99%
“…Finally, we note that these mutations occur within the same intron as retroviral integration sites described in 2 cases of gene therapyinduced T-ALL (supplemental Figure 8). 22,26 This raises the possibility that formation of aberrant promoters and enhancers, either by mutation or retroviral insertion, occur at preferred rather than random sites in the noncoding genome. For personal use only.…”
Section: Org Frommentioning
confidence: 99%
“…23,27 Clinical trials that utilized gamma-retroviral mediated ex vivo gene transfer to treat X-linked severe combined immunodeficiency and Wiskott-Aldrich syndrome have reported insertional mutagenesis by the gene therapy vector, which caused leukemia in patients. 28,29 Because the rAAV transgene exists in a predominately episomal state and integrates at a very low frequency following rAAV transduction, the chances of insertional mutagenesis by a rAAV transgene are greatly reduced in comparison with retroviral and lentiviral vectors, which usually integrate into the host genome. However, an increased incidence in hepatic carcinoma (HCC) in mice after rAAV gene delivery has been reported, and some of these studies have shown that insertional mutagenesis by rAAV was the most likely cause of the HCC.…”
Section: -19mentioning
confidence: 99%
“…7,8 Preclinical studies and additional clinical trials for SCID-X1 and Wiscott-Aldrich syndrome have continued to show similar or even higher rates of oncogenesis as a severe adverse side effect of retroviral hematopoietic stem cell (HSC) gene therapy. [9][10][11] These side effects are caused by enhancer elements within integrated vector proviruses that activate nearby proto-oncogenes. 7,[11][12][13][14][15][16] Advanced designs of retroviral vectors have eliminated or greatly reduced the native retroviral enhancer elements in the long terminal repeats (LTRs), significantly increasing the safety of modern vectors.…”
Section: Introductionmentioning
confidence: 99%